Development of an Aboge-Based Islamic History E-Module in the Merdeka Curriculum to Strengthen Local History at MAN Purbalingga - Awal Tri Riyadi (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
The integration of local history into history learning is essential for strengthening students’ historical awareness and cultural identity. However, the availability of digital teaching materials that incorporate local wisdom within the Merdeka Curriculum remains limited. This study aimed to develop an Islamic Aboge-based e-module as a local history learning resource for tenth-grade students at MAN Purbalingga. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. Data were collected through observation, interviews, questionnaires, and documentation involving subject matter experts, media experts, history teachers, and students. The feasibility of the developed e-module was analyzed using descriptive qualitative and quantitative techniques. The findings indicate that the developed e-module achieved a very high level of feasibility. Material expert validation obtained an average score of 4.72 (94%), media expert validation obtained 4.64 (92.8%), and teacher validation obtained 4.60 (92%). Small-group and large-group trials also demonstrated positive student responses, with feasibility percentages of 88% and 87%, respectively. These findings suggest that the developed e-module is suitable for supporting contextual local history learning and can be utilized as an alternative digital teaching material in the implementation of the Merdeka Curriculum.